Effects of different metals on adhesive wear behaviour of alloy surface produced by TIG process - Korkut, M. H.; Gok, M. S. (Taylor & Francis Ltd, 2008)
Low carbon steel surfaces were alloyed with composite powders using the tungsten inert gas welding method. After the alloying process, the effects of cladding surface on the microstructural characteristics and adhesive wear of the alloyed samples were examined. The sliding wear behavior of samples was investigated in a block on ring apparatus under the loads of 20, 40, 60 and 80 N respectively. In the experimental investigation, a low carbon steel surface was alloyed with austenitic stainless steel powder and austenitic stainless steel powder mixed with 4.5% Co, Mo and Ti particles respectively. Following surface alloying, conventional characterisation techniques, such as optical microscopy, scanning electron microscopy, energy dispersive spectrograph and X-ray diffraction, were used to study the microstructure of the alloyed zone. Examination of the microstructure revealed the presence of M23C6 carbides, solid melt phases and intermetallic phases, such as Ni3Ti, depending on the alloying element in the composite. As the amount of the reinforcing material increased, the saturation rates for the samples decreased, while their hardness increased. The adhesive abrasion tests conducted revealed that temperature input plays a significant role on the microstructure characteristics, which positively affected the adhesive abrasion values of the samples. Consequently, the tungsten inert gas welding method was successfully used for the surface alloying of low carbon steels.
Keywords: Surface and coating; Tungsten inert gas welding; Alloying; Adhesive wear